Recepción y apropiación estética de la obra musical de Violeta Parra en Europa (1954-1990) - Javier Rodriguez Aedo (Nuevo mundo - Mundos Nuevos, 2018)
In this article, we reflect on the international repercussions of Violeta Parra’s musical work from the point of view of the European audience. By means of the use of musical reviews and articles published in the press between 1956-1990 in Spain, France, Italy, and Germany, we intend to stablish out the aesthetic and ideological dimensions of the songwriter’s work in Europe, this last with a particular emphasis on two concepts, reception and appropriation. Given that the presence of Violeta Parra in Europe precedes the context of Chilean exile, at first, the reception of her work was not much different from the exoticism that defines the relationships given between Europe and Latin Folk Music. In this scenario, the military coup of 1973 not only played a crucial role for the international diffusion of Chilean popular music, but also for the achievement of a new reading of Violeta Parra’s work in Europe. Thus, this new European reading of Violeta Parra gradually gave way to other values regarding her work, among which ‘universality’ becomes central.